Small intestinal bacterial overgrowth and nonalcoholic fatty liver disease: a systematic review and meta-analysis. Issue 5 (May 2020) - Wijarnpreecha, Karn; Lou, Susan; Watthanasuntorn, Kanramon; Kroner, Paul T.; Cheungpasitporn, Wisit; Lukens, Frank J.; Pungpapong, Surakit; Keaveny, Andrew P.; Ungprasert, Patompong
Abstract : Objectives: Recent studies have suggested that small intestinal bacterial overgrowth (SIBO) could be a predisposing factor for nonalcoholic fatty liver disease (NAFLD) although the results were inconsistent. This systematic review and meta-analysis was conducted with the aim to summarize all available data. Methods: A comprehensive literature review was conducted utilizing MEDLINE and EMBASE databases through September 2018 to identify all studies that compared the risk of NAFLD among patients with SIBO versus those without SIBO. Effect estimates from each study were extracted and combined together using the random effect, generic inverse variance method of DerSimonian and Laird. Results: A total of 10 studies with 1093 participants fulfilled the eligibility criteria and were included in the meta-analysis. A significant association between NAFLD and SIBO was observed with the pooled odds ratio of 3.82 (95% confidence interval, 1.93–7.59; I 2 65%). Funnel plot is relatively symmetric and is not suggestive of the presence of publication bias. Conclusion: A significant association between NAFLD and SIBO was observed in this meta-analysis. Abstract : Supplemental Digital Content is available in the text.